Role of vitamin D in controlling vertigo: a review - Swain, Santosh Kumar (International Journal of Research in Medical Sciences, 2024)
Vertigo is a disabling symptom that has a high recurrence rate and interferes with day-to-day functioning. Vertigo is frequently caused by Meniere's diseases and benign paroxysmal positional vertigo (BPPV). The most prevalent neuro-ontological condition causing vertigo is BPPV. Vertigo attacks that last only a few seconds and are brought on by changing the head's position with respect to gravity are the hallmark of BPPV. There is a suggestion that vitamin D deficiencies and BPPV and Meniere's diseases are positively correlated. However, there is not much awareness among clinicians about association between vitamin D deficiency and certain etiologies of vertigo. After taking vitamin D supplements, vertigo attacks stop happening. Supplementing with vitamin D may be beneficial for patients with low vitamin D levels who have BPPV and Meniere's disease. This review's goal is to discuss about how vitamin D helps to treat vertigo, especially BPPV and Meniere's disease.